Assessment of Occupational Noise Exposure among Groundskeepers in North Carolina Public Universities - Jo Anne G. Balanay; Gregory D. Kearney; Adam J. Mannarino (SAGE Publishing, 2016)
Groundskeepers may have increased risk to noise-induced hearing loss due to the performance of excessively noisy tasks. This study assessed the exposure of groundskeepers to noise in multiple universities and determined the association between noise exposure and variables (ie, university, month, tool used). Personal noise exposures were monitored during the work shift using noise dosimetry. A sound level meter was used to measure the maximum sound pressure levels from groundskeeping equipment. The mean Occupational Safety and Health Administration (OSHA) and National Institute for Occupational Safety and Health (NIOSH) time-weighted average (TWA) noise exposures were 83.0 ± 9.6 and 88.0 ± 6.7 dBA, respectively. About 52% of the OSHA TWAs and 77% of the NIOSH TWAs exceeded 85 dBA. Riding mower use was associated with high TWA noise exposures and with having OSHA TWAs exceeding 85 and 90 dBA. The maximum sound pressure levels of equipment and tools measured ranged from 76 to 109 dBA, 82% of which were >85 dBA. These findings support that groundskeepers have excessive noise exposures, which may be effectively reduced through careful scheduling of the use of noisy equipment/tools.